A Systematic Review on Application of AI in Telecom Industry - Gupta, Mukesh Chand; Goyal, Ruchi (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Practices for performance reviews are very important for improving the efficiency of businesses and the work of their employees in many fields. With the rise of artificial intelligence (AI), standard ways of evaluating performance are changing in big ways, especially in the telecoms business. The goal of this thorough study is to look into how performance review methods are used across industries, with a focus on how AI is used in the telecom industry.A thorough screening process is used to choose articles that meet certain criteria for inclusion. This leads to a final group of 45 studies that will be analyzed.In the telecom industry, AI technologies like machine learning, natural language processing, and predictive analytics are being used more and more in performance reviews to make decisions easier and handle employees better.The review also talks about some of the benefits of performance review systems that use AI, such as real-time feedback, individual growth plans, and data-driven insights that help managers make decisions. The review also finds holes in the current research, like the fact that there isn't a lot of real-world data on how AI affects employee success and business results in the telecom industry over the long term. It is suggested that more study be done to fill in these gaps and find out how AI-driven performance reviews affect how well a company works, how happy its workers are, and how to handle human resources strategically in the fast-paced world of telecommunications and other industries.